IDENTIFIKASI KESESUAIAN TUTUPAN LAHAN RUMAH DENGAN KOEFISIEN DASAR BANGUNAN (KDB) MENGGUNAKAN CITRA QUICKBIRD DI PERUMNAS BANYUMANIK KOTA SEMARANG (Geo-Image, 2016)
This study aims to determine the type of land cover in Perumnas Banyumanik, know how big the suitability of land cover homes in Housing Banyumanik with the provisions of the RDRTK district Banyumanik, and determine the level of accuracy Quickbird imagery to monitor land cover homes in Perumnas Banyumanik. The sample in this study was the house in Perumnas Banyumanik simple random sampling or acak sederhana. Technical data used is a documentary, observation and interpretation. The research results show that 1) Quickbird imagery interpretation results of land cover in the housing Banyumanik is building cover, Dungeon vegetation and dungeon open land green. 2) Suitability of land cover in Perumnas Banyumanik house shows the overall parcel is not in accordance with the provisions RDTRK KDB number a maximum of 60%. 3) Accuracy Quickbird imagery in this study concluded that the Quickbird imagery is not recommended to measure the area of parcels home.